Effect of cultivars and weed management practices on weeds, productivity and profitability in zero-till direct-seeded rice (Oryza sativa) - SINGH, ANIMESH; SINGH, YASHWANT; SINGH, RAGHAVENDRA; UPADHYAY, PRAVIN KUMAR; KUMAR, RAKESH; SINGH, RAJIV KUMAR (The Indian Journal of Agricultural Sciences, 2019)
A field study was carried out during the two consecutive kharif seasons of 2012 and 2013 at the Agricultural Research Farm, Institute of Agricultural Sciences, Banaras Hindu University, Varanasi, to evaluate the effect of cultivars and weed management practices on weed dynamics, yield attributes, yields and economics in zero-till direct-seeded rice (Oryza sativa L.). The dominant weed flora were Echinocloa colona, Echinocloa crus-galli, Cynodon dactylon, Cyperus rotundus, Cyperus iria, Caesulia auxillaries and Eclipta alba. Among rice cultivars, Arize-6129 had minimum weed density (425.9 and 480.1/m) and dry weight (76.7 and 86.4 g/m2), and maximum of grain yield (4.29 and 4.12 t/ha) during both the years, respectively. Among the weed management practices, application of bispyribac sodium + azimsulfuron (25 g +35 g/ha) + 0.25% NIS (post-emergence) at 15-20 DAS proved to be most effective in minimizing the weed density, weed dry weight and increased rice grain yield (4.33 and 4.16 t/ha, respectively). Arize-6129 produced maximum net returns (`40402 and 37804/ha) and benefit: cost ratio (1.61 and 1.51) and economic efficiency (`316 and 298/ha day), respectively during both the years. Among weed management practices, application of bispyribac sodium + azimsulfuron (25 g +35 g/ha) + NIS (0.25%) was the most economical and efficient.